The Timing of Stroke Care Processes and Development of Stroke Associated Pneumonia: A National Registry Cohort Study - Lobo Chaves, Marco Antonio; Gittins, Matthew; Bray, Benjamin; Vail, Andy; Smith, Craig J. (Frontiers in Neurology, 2022)
Introduction Timely stroke care can result in significant improvements in stroke recovery. However, little is known about how stroke care processes relate to complications such as the development of stroke associated pneumonia (SAP). Here we investigated associations between stroke care processes, their timing and development of SAP. Methods We obtained patient-level data from the Sentinel Stroke National Audit Programme for all confirmed strokes between 1st April 2013 and 31st December 2018. SAP was identified if new antibiotic initiation for pneumonia occurred within the first 7 days of admission. Time to key stroke care processes in the pre-hospital, hyperacute and acute phase were investigated. A mixed effects logistic regression model estimated the association between SAP (Odds ratios [OR] with 95% CI) and each process of care after controlling for pre-determined confounders such as age, stroke severity and comorbidities. Results SAP was identified in 8.5% of 413,133 patients in 169 stroke units. A long time to arrival at a stroke unit after symptom onset or time last seen well [OR (95% CI) = [1.29 (1.23 to 1.35)], from admission to assessment by a stroke specialist [1.10 (1.06 to 1.14)] and from admission to assessment by a physiotherapist [1.16 (1.12 to 1.21)] were all independently associated with SAP. Short door to needle times were associated with lower odds of SAP [0.90 (0.83 to 0.97)]. Conclusion Times from stroke onset and admission to certain key stroke care processes were associated with SAP. Understanding how timing of these care processes relate to SAP may enable development of preventive interventions to reduce antibiotic use and improve clinical outcomes.